2019
DOI: 10.1111/ppa.13071
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex real‐time PCR assays for the detection and identification of Heterobasidion species attacking conifers in Europe

Abstract: Four species of the destructive forest pathogen Heterobasidion annosum sensu lato (s.l.) are present in Europe: H. annosum sensu stricto (s.s.), H. abietinum and H. parviporum are native species, while H. irregulare is a non‐native invasive species currently reported only in Italy, yet recommended for regulation throughout Europe. In this study, real‐time PCR detection tests were developed for each of the four species, which can be used simultaneously or individually thanks to probes labelled with species‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…For example, the primers used for specific detection of E. alphitoides may amplify DNA from powdery mildew species in the same clade, which share highly similar ITS sequences but do not affect oaks (Chen et al, 2015). However, primers targeting single copy genes to differentiate species within the H. annosum complex, designed for diagnostic purposes (Ioos et al, 2019), failed to detect any target in aerobiological samples (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the primers used for specific detection of E. alphitoides may amplify DNA from powdery mildew species in the same clade, which share highly similar ITS sequences but do not affect oaks (Chen et al, 2015). However, primers targeting single copy genes to differentiate species within the H. annosum complex, designed for diagnostic purposes (Ioos et al, 2019), failed to detect any target in aerobiological samples (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 30 mg of tissue was processed with DNeasy Plant Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions, to a final elution volume of 50 μl. The real-time PCR assays for detection of Heterobasidion annosum and H. parviporum , the two Heterobasidion species present in Norway, were conducted in singleplex conditions in Takyon Low ROX Probe MasterMix dTTP Blue (Eurogentec, Seraing, Belgium), with primers and probes described by Ioos et al ( 2019 ) and synthesized by Eurogentec.…”
Section: Methodsmentioning
confidence: 99%
“…The H. parviporum qPCR assay included the forward primer 5′-CAATCGTATGGGGTCATTGTAA-3′, the reverse primer 5′-CACATCCGCCATGTCCC-3′ and the probe TAMRA-GATCTGCGAGCCCGACGAACCG-BHQ2. Real-time PCR amplifications were carried out in an Applied Biosystems ViiA 7 system (ThermoFisher, Waltham, MA, USA) with standard, instead of fast, cycling and the same PCR cycling parameters as described by Ioos et al ( 2019 ). Two technical replicates were prepared for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…A new PCR assay has been developed to also distinguish Fusarium circinatum and Caliciopsis pinea that cause comparable symptoms on P. radiata in the initial stages of colonization (Luchi et al 2018). All four European species of Heterobasidion attacking conifers may be simultaneously detected in two reactions (Ioos et al 2019b).…”
Section: Disease Controlmentioning
confidence: 99%